2020
DOI: 10.1002/hed.26159
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer histological subtypes based on tumor size: National perspective

Abstract: Background Thyroid tumor size is an important prognostic factor. The aim of this study is to examine the histological subtypes and management of thyroid cancer based on tumor size (≤4 cm vs >4 cm). Methods Retrospective cohort study utilizing the National Cancer Database, 2004‐2014. Results A total of 152 387 patients were included, 13 614 (8.9%) of whom had a tumor size >4 cm. Histological subtypes of tumors >4 cm were: 69.6% papillary thyroid carcinoma, 17.5% FTC, 7.9% HCC, and 2.8% medullary thyroid carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Patients age >65 had a decreased survival rate and the risk of death increases by 5.2% for each additional year(3). Previous study found that tumor size >4 cm had signi cantly worse survival outcome compared to those diameter ≤4 cm (12). The results of this study veri ed the previously established conclusions that lesion size is associated with a decreased survival trend (13,14).…”
Section: Discussionsupporting
confidence: 88%
“…Patients age >65 had a decreased survival rate and the risk of death increases by 5.2% for each additional year(3). Previous study found that tumor size >4 cm had signi cantly worse survival outcome compared to those diameter ≤4 cm (12). The results of this study veri ed the previously established conclusions that lesion size is associated with a decreased survival trend (13,14).…”
Section: Discussionsupporting
confidence: 88%
“…Medullary thyroid carcinoma (MTC) arises from the parafollicular C cells of the thyroid, accountings for only 5–10% of all thyroid cancers worldwide, however, despite its rarity, MTC is responsible for 8–13% of thyroid cancer-related deaths [ [ 1 , 2 ]]. Approximately 75% of the patients have no family history of MTC, while the rest show a genetic form of the RET mutation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Central vascularization and a high rate of metabolic activity are important characteristics of malignant nodules [ 11 ]. Due to increased blood flow, malignant nodules could have a higher and more constant temperature than the surrounding region or benign nodules [ 12 , 13 , 14 ]. The verification (or contradiction) of these statements is the aim of this study.…”
Section: Introductionmentioning
confidence: 99%